Structure-function relationships among wild-type variants of Staphylococcus aureus beta-lactamase: importance of amino acids 128 and 216. - Voladri, R K (1996)
beta-Lactamases inactivate penicillin and cephalosporin antibiotics by hydrolysis of the beta-lactam ring and are an important mechanism of resistance for many bacterial pathogens. Four wild-type variants of Staphylococcus aureus beta-lactamase, designated A, B, C, and D, have been identified. Although distinguishable kinetically, they differ in primary structure by only a few amino acids. Using the reported sequences of the A, C, and D enzymes along with crystallographic data about the structure of the type A enzyme to identify amino acid differences located close to the active site, we hypothesized that these differences might explain the kinetic heterogeneity of the wild-type beta-lactamases. To test this hypothesis, genes encoding the type A, C, and D beta-lactamases were modified by site-directed mutagenesis, yielding mutant enzymes with single amino acid substitutions. The substitution of asparagine for serine at residue 216 of type A beta-lactamase resulted in a kinetic profile indistinguishable from that of type C beta-lactamase, whereas the substitution of serine for asparagine at the same site in the type C enzyme produced a kinetic type A mutant. Similar bidirectional substitutions identified the threonine-to-alanine difference at residue 128 as being responsible for the kinetic differences between the type A and D enzymes. Neither residue 216 nor 128 has previously been shown to be kinetically important among serine-active-site beta-lactamases.